‘A living, moving exhibition’: Ukraine Museum opens in Berlin air-raid bunker - Connolly, Kate (The Guardian, 2026)
Exhibits pay homage to Ukrainians’ resilience and bring home the reality that war is going on in Europe
Ukraine
Keywords: Europe; Germany; Museums; Ukraine; World news